Ricardo Güiraldes - Becco, Horacio Jorge, 1924-; Güiraldes, Ricardo, 1886-1927. (Buenos Aires : Universidad de Buenos Aires. Instituto de literatura argentina "Ricardo Rojas", 1959)
reinventariado por duplicación de inventario 29/960
Keywords: Bibliografias